Unveiling the connections: Chlorpyrifos and its association with breast cancer - Eliana Estrella Akselrad; María de la Cabeza Fernández; Paula Moyano; María Victoria Naval (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2023)
Chlorpyrifos, a broad-spectrum insecticide categorized within the organophosphate family, is recognized for its potent inhibition of the enzyme Acetylcholinesterase (AChE), resulting in the manifestation of cholinergic syndrome in humans. Beyond its well-established toxicity in the central nervous system, recent studies have explored additional pathways through which this pesticide may adversely impact human health.  Breast cancer, characterized by the uncontrolled proliferation of epithelial cells in the mammary gland, stands as the most diagnosed cancer in women and is a leading global cause of female cancer-related deaths.  Chlorpyrifos, extensively employed worldwide for pest control in agriculture, domestic settings, and industries, has notably faced recent bans in the European Union, marking a significant regulatory shift. This bibliographical review aims to unravel the intricate mechanisms by which chlorpyrifos may contribute to the development of breast cancer.  Collating findings from human studies, as well as in vitro and in vivo research spanning the past decade, the review sheds light on chlorpyrifos as a potent endocrine disruptor. It influences female sex hormones, exhibits estrogenic effects on breast cancer cells, and induces alterations in breast tissue. Additionally, chlorpyrifos acts as an agonist of Estrogen Receptor α(ERα) and Aryl hydrocarbon Receptor (AhR), contributing to cell proliferation, oxidative stress, and engaging epigenetic and angiogenic mechanisms.  This comprehensive review underscores the compelling association between chlorpyrifos exposure and mammary cancer. It emphasizes the urgent need for further research on pesticide usage to mitigate potential adverse health consequences.